Deep learning for real world face alignment - Bulat, Adrian (2019)
Face alignment is one of the fundamental steps in a vast number of tasks of high economical and social value, ranging from security to health and entertainment. Despite the attention received from the community for more than 2 decades and the success of cascaded regression based approaches, many challenges were yet to be solved, such as the case of near-profile poses and low resolution faces.